MATHEMATICS LEARNING STRATEGY BOOK ON PEDAGOGICAL CONTENT KNOWLEDGE FOR ELEMENTARY SCHOOL PRE-SERVICE TEACHERS - Mukti Sintawati; Asih Mardati; Ginanjar Abdurrahman (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2022)
The goal of this study is to describe the impact of a mathematics learning strategy book on elementary school pre-service teacher' pedagogical content knowledge. The research method used is experimental research with poor experimental methods. A one-group pretest-posttest design was used. This study's sample size is 94 pre-service teachers or elementary school teacher education students. Tests and assessment sheets are data collection instruments for measuring PCK. The test is used to determine PK and CK levels. The Quizizz application is used to administer the test, which is in the form of multiple choice questions. PCK is measured using a score sheet. The data is analyzed using descriptive statistics and inferential statistics. To explain the distribution of PCK data, descriptive statistics are used. To test the research hypotheses, inferential statistics are used. The paired sample t-test was used to test the hypothesis. The results show that pre-service teachers' PCK is in the high range. The hypothesis test results show that the mathematics learning strategy book used in learning is effective against pre-service teachers' PCK. Mathematics learning strategy books used in elementary schools not only contain theory and material, but also provide examples of student worksheets based on specific strategies/methods. This is what helps pre-service teachers understand so that it has an impact on increasing PCK.